CBC y la enseñanza de la matemática - IAEIS, Gustavo comp. (A-Z, 2002)
Otros autores: BRESSAN, Ana; CHEMELLO, Graciela; DIAZ, Adriana; GYSIN, Liliana M.; HANFLING, Mirta; PANIZZA, Mabel; PARRA, Cecilia; SAVON, Silvana; ESPERANZA, Gladys; GOTBETER, Gustavo